Afeksi dalam Teologi Jonathan Edwards serta Implementasinya dalam Kehidupan Kristen - Grace Emilia (Sekolah Tinggi Teologi Baptis Indonesia, 2020)
The purpose of this article is to examine the term ‘affections’ in Jonathan Edwards’ theology written in the 18th century in one of his masterpieces, “A Treatise Concerning Religious Affections.” Affection is a terminology in modern psychology, a discipline of science that just existed in the middle of the 19th century. The study, conducted using the descriptive qualitative method, tries to see whether the term carries the same meaning by exploring its background, definition, characteristic, significance and implementation in the Christian life. The conclusion shows that Edwards talks about the nature of human heart or inclination or will where ratio and emotions interact to influence decision makings. Having the right heart or holy affection is the telos of a Christian life.